Metaphor Analysis on Color Lexicon with Plant Attributes in Madurese Language - Nurul Fadhilah; Wakit Abdullah Rais; Dwi Purnanto (Bina Nusantara University, 2019)
The research aimed to describe the Madurese color lexicons with plant attributes and to analyze those lexicons metaphorically. This research engaged 18 informants to denote Madurese color lexicons by showing 139 color cards. The referential comparison method was followed by sorting the decisive element technique through referential competence-in-dividing, and Connect Compare Equate as the advanced technique was used as the data analysis method. The research finds that 53 color lexicons with plant attributes in 8 Madurese color lexicons, namely potѐ ‘white’, celleng ‘black’, mѐra ‘red’, bhiru ‘green’, konѐng ‘yellow’, cokklat ‘brown’, bhiru ‘blue’, and bungo ‘purple’. Furthermore, these plant attributes can be classified into fruits, flowers, vegetables, seeds, spices, leaves, trees, part of the tree, and part of the fruit. The domination of plant attributes in Madurese color lexicons emerges due to the sociocultural factors embodied in Madurese ethnic group itself, those are (1) farming is Madurese main way of living, (2) Madurese ethnic group respect the nature as the place where they can pray and thank God, and (3) some objects associated with color lexicons are abundantly available at their surroundings, thus they frequently use it in their daily life.